2002
DOI: 10.1097/00005344-200210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Protection From AMP 579 Can Be Added to That From Either Cariporide or Ischemic Preconditioning in Ischemic Rabbit Heart

Abstract: AMP 579, an adenosine A /A receptor agonist, is cardioprotective when administered at reperfusion. Pretreatment with the Na /H exchanger inhibitor cariporide or ischemic preconditioning (PC) also limits infarct size. To gain insight into the mechanism of AMP 579 we investigated whether its protection could be added to that from either cariporide or PC. rabbit hearts were subjected to 45 min of regional ischemia followed by 3 h of reperfusion. Infarct size in the control group was 55.8 +/- 3.9% of the risk zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In addition, Zhao et al reported that adenosine at reperfusion can block ischemia-reperfusion-induced apoptosis by activating A 2 receptors [36]. Recently, Xu et al have demonstrated that AMP579, a novel adenosine A 1 /A 2 receptor agonist, given at reperfusion significantly reduces infarct size in rabbit hearts [37,38], and that the activation of adenosine A 2 receptors at reperfusion accounts for the protective effects of AMP579 [37]. Interestingly, Yang et al have documented that the NECA-induced cardioprotection against infarction at reperfusion was blocked by both the adenosine A 2 receptor antagonist CSC and the NOS inhibitor l-NAME [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zhao et al reported that adenosine at reperfusion can block ischemia-reperfusion-induced apoptosis by activating A 2 receptors [36]. Recently, Xu et al have demonstrated that AMP579, a novel adenosine A 1 /A 2 receptor agonist, given at reperfusion significantly reduces infarct size in rabbit hearts [37,38], and that the activation of adenosine A 2 receptors at reperfusion accounts for the protective effects of AMP579 [37]. Interestingly, Yang et al have documented that the NECA-induced cardioprotection against infarction at reperfusion was blocked by both the adenosine A 2 receptor antagonist CSC and the NOS inhibitor l-NAME [5].…”
Section: Discussionmentioning
confidence: 99%
“…One to four cycles of ischemic PC were selected for our studies in the isolated working rabbit heart, because generally one to four PC cycles protected the ischemic myocardium, in various degree, against the incidence of reperfusion-induced damage in the models of PC in intact myocardium (10,20,26,29,41,42,55,57,58,72). PC studies have been carried out after 8 weeks of cholesterol diet, and comparisons were made with the age-matched noncholesterolemic groups.…”
Section: Ischemia and Reperfusion In Preconditioned Heartsmentioning
confidence: 99%
“…On the other hand, AMP579 is a unique agent with high affinity for both adenosine A 1 and A 2A receptors, and it has been shown to exert much less hemodynamic effects in vivo [10,[26][27][28][29]. Treatment with AMP579, both prior to ischemia and during reperfusion, reduces in vivo infarct size in several species [26][27][28][29][30][31], due to its ability to activate both adenosine A 1 and A 2A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with AMP579, both prior to ischemia and during reperfusion, reduces in vivo infarct size in several species [26][27][28][29][30][31], due to its ability to activate both adenosine A 1 and A 2A receptors. We have recently reported that pretreatment with AMP579 dose-dependently attenuated in vivo myocardial stunning, with only minor, transient reductions in HR and MAP [10].…”
Section: Discussionmentioning
confidence: 99%